Exploring the Wound Healing Activity of Turmeric Oil Based Emulgel through Topical Drug Delivery - Vibha; Bahadur, Shiv; Bajpai, Meenakshi (International Journal of Pharmaceutical Investigation, 2025)
Introduction Wounds may be known as any damage or distortion to the normal structural and functional of skin, if left untreated it can be more dangerous, reaching in subcutaneous tissue and serious harm to other structure. After a wound, subcutaneous tissue exposed, providing a warm, moist, and nutrient-rich condition that is favourable to microbial colonization and growth. Recent research has indicated that the use of emulsion-based gel formulation, topical medication delivery systems may present an appealing treatment alternative for wounds. Therefore, objective of this research was to develop an emulgel containing turmeric oil for the management of wounds. This ground-breaking medication may provide an alternative approach to wound treatment. Materials and Methods The emulgel was developed by various turmeric oil-based emulsions with Smix (surfactant and co-surfactant), which were further incorporated into the gel base. Gel bases were composed of different concentrations of carbopol 940. The prepared emulgel was evaluated for different parameters. Results and Discussion The developed formulations were evaluated on the basis of different parameters such as pH, viscosity, Extrudability, Spreadability, Drug Content, and Anti-microbial studies. the physical properties of emulgel satisfied the necessary standards. These eight emulgel formulation efficaciously inhibit the growth of organism. The present research work indicates the emulgel was effective against gram negative and gram positive bacterial. Zone of inhibition was found between 2.1 to 8.9 µM. The highest ZOI was measured against Bacillus subtilis. Conclusion The emulgel of turmeric essential oil showed the most promising results for wound management by inhibiting microorganisms that form biofilm and delaying the wound healing process. These results provide captivating novel possibilities for wound management and emphasize the significance of ongoing research in this field.
Keywords: Essential oil; Turmeric oil; Emulgel; Carbopol 940; Wounds Healing; Topical formulation